Teaching Students with Learning Difficulties or Disabilities: Regular Education Teachers' Professional Development and Practices - Helena Inês; José Augusto Pacheco; Marta Abelha; Filipa Seabra (MDPI AG, 2022)
This article focuses on how curricular and pedagogical differentiation for students of special education is perceived by teachers of the second cycle of basic education in Portugal. The objectives of this research were (i) to inquire about the teachers' perceptions regarding their training path and their training needs; (ii) to characterize the teaching practices of teachers, aimed at students of special education; and (iii) to learn the perceptions of these teachers regarding their curricular and pedagogical practices directed at students of special education-this called for an interpretative methodology. The data were collected through semi-structured interviews and subjected to content analysis. The results indicate a widespread concern with teachers' current professional development and the management of diversity. The respondents' perceptions, shown as favorable to change, are in line with personalized work, enhancing visible contributions to students' personal and social development.